Analisis Pengaruh Return on Equity (ROE) dan Debt to Equity Ratio Terhadap Return Saham Perusahaan Energi Periode 2020-2024 - Wahidah Nazmi Lailia; Annisa Pratiwi Sundari; Mila Salbiyah; Pina Aulia Maharani (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The purpose of this study is to examine the influence of fundamental factors, as seen from the Return on Equity (ROE) and Debt to Equity Ratio (DER), on stock returns. The analytical method used is panel data regression analysis. This study used six energy sector companies listed on the Index Stock Exchange (IDX) for the 2020-2024 period. The sample determination in this study used a purposive sampling method. Based on the analysis of the research results, ROE has a significant effect on stock returns, while DER has no effect on stock returns. The coefficient of determination from the research results of the two variables on stock returns is 37.6%, while the remaining 63.3% is influenced by other factors not included in the research model.